The Development Of Makyong Acting Training Method For Environment Of Traditional Theater Courses - Ilham Rifandi (Gondang: Jurnal Seni dan Budaya, 2022)
This study aims to develop a Makyong acting training method based on the Malay tradition for enrichment in the North Sumatra Traditional Theater course at the UNIMED Performing Arts Study Program. In particular, this study aims to: (1) be able to interpret Malay advice as spiritual values; (2) identifying Malay dance techniques to prepare for body movements; (3) Identifying the Malay pantun tradition as the improvisational power of makyong actors. This study was designed with a research and development approach. This research was followed up by developing methods and applying methods in training and performances. In analyzing the data the author uses qualitative analysis techniques. As a reference in preparing the training model, the author uses the folklore approach, actor dramaturgical theory from Eugenio Barba and Asrul Sani's postcolonial acting approach as a reference in developing acting training methods.